Report on Access to Fund Resources During 2005. (Policy Papers; Policy Paper, 2006)
In the context of a relatively benign international environment with limited balance of payments needs, recourse to Fund resources has declined across several dimensions: fewer GRA arrangements; lower outstanding Fund resources; and a smaller average access under new PRGF arrangements.